Preparation of Cellulose Nanocrystals Bio-Polymer from Agro-Industrial Wastes: Separation and Characterization. Issue 9 (November 2016) - Mazlita, Y.; Lee, H.V.; Hamid, S.B.A.
Lignocellulosic biomass from oil palm agro-industrial waste is highly potential to be valorised into cellulose polymer in nanoscale, which is useful for various applications. The present study discussed the synthesis of cellulose nanocrystal (CNC) from oil palm trunk (OPT) biomass via chemical-sonication process. The effect of pretreated alkali-bleached OPT and H2 SO4 acid hydrolysed (40% and 60% w/w) cellulose were investigated by utilizing X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA). Biomass crystallinity, thermal stability and chemical functional group suggested that the pretreatment process has successfully isolated cellulose from OPT, which indicated the removal of lignin, hemicellulose and impurities from the palm fibers. Furthermore, SEM and TEM images revealed that CNC40 and CNC60 were observed in rod-shaped structure with the dimension of 100.00 nm (L) x 27.50 nm (d) and 95.00nm (L) x 25.00nm (d), respectively, and corresponded to the aspect ratio of 3.63 and 3.80, respectively. In the presence of sonication condition, the study suggested that both 40 and 60%w/w of H2 SO4 rendered active effect for acid depolymerisation of cellulose at 45 °C and 15 min of time. Thus, this can concluded that milder acid (40%w/w) was able to produce cellulose in nanosizes under mild operating condition with the assistant of sonication effect.